2014
DOI: 10.1021/ac5025446
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Dissolved Inorganic Carbon Species and of the pH of Alkaline Solutions Exposed to CO2 under Pressure: A Novel Approach by Raman Scattering

Abstract: Dissolved inorganic carbon (DIC) content of aqueous systems is a key function of the pH, of the total alkanility (TA), and of the partial pressure of CO2. However, common analytical techniques used to determine the DIC content in water are unable to operate under high CO2 pressure. Here, we propose to use Raman spectroscopy as a novel alternative to discriminate and quantitatively monitor the three dissolved inorganic carbon species CO2(aq), HCO3(-), and CO3(2-) of alkaline solutions under high CO2 pressure (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…However, this size effect could be related to the presence of the neutral PEO segment on 3 which could limit the growth of the microparticles. The crystal size appears quite similar to those obtained with HA 88 showing that the templating polymer has few, if any, influence on the vaterite nanograin size. Moreover, PEO-b-PBYPCOOH 3 is much more efficient than PEO-b-PPDO À 6 for templating the calcium carbonate particles, most probably due to a higher calcium ion complexation ability and (Table S1, ESI †) is clearly negative indicating the presence of the stabilizing copolymers at their surface.…”
Section: Calcium Carbonate Microparticle Formationsupporting
confidence: 72%
See 2 more Smart Citations
“…However, this size effect could be related to the presence of the neutral PEO segment on 3 which could limit the growth of the microparticles. The crystal size appears quite similar to those obtained with HA 88 showing that the templating polymer has few, if any, influence on the vaterite nanograin size. Moreover, PEO-b-PBYPCOOH 3 is much more efficient than PEO-b-PPDO À 6 for templating the calcium carbonate particles, most probably due to a higher calcium ion complexation ability and (Table S1, ESI †) is clearly negative indicating the presence of the stabilizing copolymers at their surface.…”
Section: Calcium Carbonate Microparticle Formationsupporting
confidence: 72%
“…Given the wide difference of structure between 3 and HA, it is difficult to pinpoint one specific structural parameter as responsible for the difference in the CaCO 3 particle size. 88 Based on the analysis of the broadening of the XRD peaks using the Debye-Sherrer equation, the size of the vaterite crystals that compose both types of microspheres is approximately 25 AE 5 nm. In addition, the high carboxylic acid density of compound 3 as compared to HA might also favor the interaction of 3 with CaCO 3 nuclei and slow down their growth.…”
Section: Calcium Carbonate Microparticle Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from application of Raman spectroscopy to molecular interactions, quantitative analytical application of Raman spectroscopy has been developed successfully in both laboratory and submarine environment at various temperature–salinity–pressure conditions because of its non‐destructive and non‐contact advantages. Indeed, the water stretching Raman band is often used as internal standard in the determination of aqueous dissolved species concentration in the molality scale . In our previous works, Ou et al found that the Raman peak area ratio (PAR = A CH4 / A H2O ) between the stretching bands of methane and water was affected by temperature and salinity, and the effect of dissolved NaCl on the PAR/mCH 4 (mCH 4 the concentration of CH 4 by mol/kg·H 2 O) became more and more significant with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the water stretching Raman band is often used as internal standard in the determination of aqueous dissolved species concentration in the molality scale. [24,[31][32][33][34][35][36][37][38][39][40][41][42][43] In our previous works, Ou et al [39,40] found that the Raman peak area ratio (PAR = A CH4 /A H2O ) between the stretching bands of methane and water was affected by temperature and salinity, and the effect of dissolved NaCl on the PAR/mCH 4 (mCH 4 the concentration of CH 4 by mol/kg·H 2 O) became more and more significant with increasing temperature. Nevertheless, the mechanism of the dependence of PAR/mCH 4 on temperature and salinity remains unclear.…”
Section: Introductionmentioning
confidence: 99%